Mutational and putative neoantigen load predict clinical benefit of adoptive T cell therapy in melanoma. Issue 1 (December 2017) - Lauss, Martin; Donia, Marco; Harbst, Katja; Andersen, Rikke; Mitra, Shamik; Rosengren, Frida; Salim, Maryem; Vallon-Christersson, Johan; Törngren, Therese; Kvist, Anders; Ringnér, Markus; Svane, Inge; et al.
Abstract Adoptive T-cell therapy (ACT) is a highly intensive immunotherapy regime that has yielded remarkable response rates and many durable responses in clinical trials in melanoma; however, 50–60% of the patients have no clinical benefit. Here, we searched for predictive biomarkers to ACT in melanoma. Whole exome- and transcriptome sequencing and neoantigen prediction were applied to pre-treatment samples from 27 patients recruited to a clinical phase I/II trial of ACT in stage IV melanoma. All patients had previously progressed on other immunotherapies. We report that clinical benefit is associated with significantly higher predicted neoantigen load. High mutation and predicted neoantigen load are significantly associated with improved progression-free and overall survival. Further, clinical benefit is associated with the expression of immune activation signatures including a high MHC-I antigen processing and presentation score. These results improve our understanding of mechanisms behind clinical benefit of ACT in melanoma. Adoptive T cell therapy (ACT) has yielded high response rates in melanoma, however 50–60% of patients experience no clinical benefit. Here, the authors identify predictive biomarkers, high non-synonymous mutation and high expressed neoantigen load, that associate with clinical benefit in ACT melanoma patients.